Genotype-specific increase in plasma concentrations of activated coagulation factor VII in response to experimental inflammation - Bennermo, Marie; Held, Claes; Ericsson, Carl-Göran; Silveira, Angela; Hamsten, Anders; Tornvall, Per (Thrombosis and Haemostasis, 2005)
There is evidence that infection and inflammation might trigger an acute coronary event, but the mechanisms are unclear. Activated factor VII (FVIIa) is a potent coagulant that is under genetic control and a potential determinant of the outcome of acute myocardial infarction. This study investigated the acute FVIIa response to experimental inflammation. Forty healthy men and women were vaccinated with 1 ml of Salmonella Typhii vaccine. Plasma levels of FVIIa, FVII antigen (FVIIag), tissue factor (TF) activity and thrombin-antithrombin complex (TAT) were measured at baseline and up to 24 hours after inoculation. All subjects were genotyped for the FVII gene Arg353Gln polymorphism. Plasma concentrations of FVIIa, but not FVIIag, increased significantly with a peak at 10 hrs after vaccination. At 24 hrs FVIIa levels had returned to baseline. The FVIIa response to vaccination was significantly greater in subjects with the ArgArg genotype compared with ArgGln subjects.TAT increased, butTF activity was unchanged after vaccination. The results are of interest from a mechanistic viewpoint, since one explanation for the link between infection and acute myocardial infarction might be activation of coagulation. However, there is a need for further studies of the role of infection and inflammation in haemostasis.
Keywords: Gene regulation; inflammatory mediators; tissue factor/factorVII